Inhuman conditions : on cosmopolitanism and human rights - Cheah, Pheng (Harvard University Press, 2006)
Through an examination of debates about cosmopolitanism and human rights, Inhuman Conditions questions key ideas about what it means to be human. Cheah links influential arguments about the new cosmopolitanism to a perceptive examination of the older cosmopolitanism of Kant and Marx, and juxtaposes them with proliferating formations of collective culture to reveal the flaws in claims about the imminent decline of the nation-state and the obsolescence of popular nationalism.